Employment Perceptions of Parolees: The Role of Perceived Barriers and Criminal Thinking. (September 2021) - Varghese, Femina P.; Skaggs, Sydney; Christie, Christina; Mark, Daniel; Swindle, Taren; Anderson, Evan; Sandlin, Luke
This study explored offenders' perception of their barriers to employment and investigated the role of criminal attitudes in parolees recently released from prison. An analysis of open-ended responses from offenders indicated that they perceived having a criminal record as the largest barrier to employment. Structural equation modeling, utilizing a cross-sectional design, indicated moderate support for a model of criminal thinking as a predictor of perceived barriers and of self-efficacy. Survey results also found that criminal attitudes have a positive direct relationship with perception of barriers in work and education, with perception of barriers increasing as criminal thinking increases. Furthermore, criminal thinking has a negative direct relationship with job search self-efficacy, with job search self-efficacy decreasing as criminal thinking increases. Criminal thinking also had an indirect relationship with career aspirations through job search self-efficacy. Findings have implications for vocational programming for parolees.